Effects of gestational low dose perfluorooctanoic acid on maternal and “anxiety-like” behavior in dams - Merrill, Alyssa K.; Conrad, Katherine; Marvin, Elena; Sobolewski, Marissa (Frontiers in Toxicology, 2022)
Pregnancy is a unique critical window with nearly ubiquitous exposure to low concentrations of endocrine disrupting chemicals, such as per- and poly-fluoroalkyl substances (PFAS). Human and animal research suggests that PFAS compounds disrupt hypothalamic-pituitary-adrenal axis function, with some evidence of altered “anxiety-like” behavior, but little is known about the potential effects on maternal mental health following exposures during pregnancy. Evaluating the consequences of gestational PFAS exposures on maternal health is essential, because approximately 1 in 10 women experience postpartum depression, often with increased anxiety. To address this gap, dams were exposed to a low dose, 0.1 mg/kg, of perfluorooctanoic acid (PFOA) from gestational day 0 to birth. Maternal behavior was then observed from postnatal days 5 to 9, and “anxiety-like” behavior was measured using open field spontaneous locomotor behavior and elevated plus maze following weaning. No difference was observed in the litter size or sex of offspring. Gestational PFOA exposure altered maternal behavior. Despite similar nursing durations, PFOA dams spent more time nursing in a flat posture and on their side, and less time in kyphosis. Despite significantly quicker first contact, PFOA dams did not return pups to the nest quicker, indicating reduced retrieval latency. At weaning, dams displayed increased “anxiety-like” behaviors in the elevated plus maze with a significantly higher mean duration in the closed arms and reduced choice frequency with significantly lower number of entries in the closed and open arms. PFOA dams showed reductions in ambulatory movement across the session. Pregnancy exposure to PFOA altered both maternal and “anxiety-like” behavior in dams. Additional assays focused on depressive-associated behaviors, such as forced swim, anhedonia, and social preference, will further delineate behavioral mechanisms. Further research on the effects of environmental contaminant exposures during pregnancy should investigate how co-exposures to other risk factors, such as stress, may enhance behavioral toxicity. Understanding how environmental contaminant exposure during pregnancy effects maternal depressive, and/or “anxiety-like” behavior is necessary for the public health protection of women.